Brahman Cross Development in Village Breeding Centre of the Sarjana Membangun Desa: Pitfall and A Lesson Learned - Yuwono, P; Sodiq, A (ANIMAL PRODUCTION, 2010)
This study was conducted to evaluate the cattle development regarding the pitfall to be lesson learned on cow-calf operation of Brahman Cross (BX) of farmer groups in Village Breeding Centre (VBC) in Central Java province.Â  Data on productivity of BX were compiled from 547 Brahman cows of 43 VBC of The Sarjana Membangun Desa (SMD) program years 2008-2009 distributed in 10 regencies. Dynamic population, calf-crop, calf and dam mortality, rate of second calving, and service per conception (S/C) were recorded. Quantitative and qualitative descriptive analyses Â were applied in this study. Cow-calf operation of Brahman Cross in 43 VBC was unsuccessful in terms of low reproductive rate for the second pregnancy and calving as well as a high rate of calf and dam mortality.Â  The rate of the second calving was 2.89%.Â  Calf and dam mortality were 17.27 and 12.23% for the SMD year 2009, meanwhile 25.67 and 7.08% Â for the SMD year 2008, respectively.Â  Cow-calf development of BX in 43 VBC with the goal of increasing cattle populations was not significant.Â  Some experiences on unsuccessful cow-calf development of BX must be taken into account and become a lesson learned for policy and program formulation in terms of cattle development through cow-calf operation of BX. The real actions through synergism and collaboration among parties (stakeholders) to solve the problems in BX development should be implemented in order to increase farmersâ income, and to achieve the main goal in the acceleration of self-sufficiency in beef production. (Animal Production 12(3): 156-162 (2010)Â Key Words: Beef cattle development, Brahman Cross, breeding, calf-crop.